Safety storage of plant genetic resources in the Arctic - Westengen, Ola T (MTT, 2008)
The Svalbard Global Seed Vault officially opened on the 26th February 2008. The Norwegian Prime Minister, Jens Stoltenberg, and Nobel Peace Price-winning environmentalist Wangari Maathai placed the first seeds in the vault during the widely media broadcasted opening ceremony. The strong symbolism in the project and its coincidence with a general increased focus on environmental and agricultural issues on the international policy agenda has already made the Seed Vault a global icon for biodiversity conservation. The vision behind the Seed Vault is to safeguard the world s crop diversity for the future by providing free of charge back-up storage for seed accessions held in conventional genbanks around the world. When reading some of the media reports about the project one can get the impression that the Seed Vault s purpose is to preserve all crop diversity in the world, forever, and all by itself. To anyone briefly familiar with the complex task of conserving plant genetic resources this is an obvious exaggeration of what the Seed Vault can offer. In this article I will give a brief outline of the Seed Vault s political and practical context and role. A vault, not a bank The Svalbard Global Seed Vault is not a gene bank. Gene banks do more than storing seeds; amongst other activities they viability test and regenerated their seed accessions when that is needed and normally they distribute seed samples to researchers, breeders and other users. The Seed Vault does not carry out such banking functions; it merely offers a safe backup site for the unique and important crop diversity held in the world s gene banks. According to FAO s database on institutions holding plant genetic resources for food and agriculture there are about 1400 of them around the world. Many of them are located in geopolitically unsafe areas, others in areas prone to natural disasters, many struggle to secure funding and maintain good management. Those are some reasons why a backup site is needed. Besides, it is only common sense to store valuable resources at more than one site it s about avoiding keeping all eggs in one basket. However, all 1400 collections of plant genetic resources can not make use of the Seed Vault, simply of the reason that they hold crops that propagate by other means than seeds. Crops such as the banana, which do not produce seeds, or that are normally propagated vegetatively, can be conserved as living plants in field-gene banks or as plant tissues grown in test tubes (in vitro) kept under extremely cold conditions that minimize their growth rate (kryopreservation). Thus, the Seed Vault is only a backup alternative for collections of crops producing orthodox seeds. This type of plants does however encompass most of our vegetables and grain and pulse crops. Operation, terms and conditions The building and its location are spectacular. Nevertheless, the facility itself is based on appropriate and cost-effective architecture and technology. The Seed Vault is located on the Arctic Archipelago Svalbard at 78° North. Three vault chambers sit at the end of a 125- metre tunnel carved out of a mountainside. The vaults are maintained at minus 18°C by means of a locally powered 10 Kw compressor, while the permafrost ensures a back-up temperature at a maximum of -4°C. The Seed Vault is located just 1,5 kilometers from the airport of the Norwegian settlement Longyearbyen and the seed boxes are scanned there 13 before transport to the vault. The facility is kept under surveillance by means of motion-, gas- and temperature- detectors. Before shipment to Svalbard the depositors must submit a minimum of information (descriptors) about each seed sample in the box. This information is both enclosed in the boxes and made publicly available through the Seed Portal at www.nordgen.org/sgsv. As an example there is already more than 72 000 samples of Oryza (rice and wild relatives of rice) from more than 100 countries stored in the Seed Vault. All holders of PGRFA are welcome to use the Seed Vault for back up of their collections, and they can do so free of charge. NordGen liaises with potential depositors with respect to the material and schedule for deposition. A Standard Deposit Agreement that lays out the terms and conditions for depositing seed samples in the Seed Vault is concluded with all depositors. The act of depositing seed samples in the Seed Vault does not affect property rights to the material. Apart from the minimum set of information that must accompany the samples black-box conditions apply and only the depositor will be able to withdraw their own samples. On the other hand it is required that the depositors distribute samples of their own stocks samples of accessions in line with the principles in the International Treaty on Plant Genetic Resources for Food and Agriculture. Governance The Norwegian Government established the Seed Vault as a service to the world community. The management and operation of the Seed Vault is done according to a three-party agreement: It is owned and administered by the Norwegian Ministry of Agriculture and Food; The Global Crop Diversity Trust provides support for the ongoing operations as well as funding for preparation and shipment of seeds from developing countries and in-trust collections held by International Agricultural Research Centres; The Nordic Genetic Resource Centre (NordGen) manages the facility. An international advisory council (including representatives of the Governing body of the International Treaty, of FAO, CGIAR, the Trust, etc.) oversees the management and operation. The initiative has received intergovernmental endorsement by the FAO Commission of Genetic Resources for Food and Agriculture. It is created in the context of the International Treaty, which provides for countries to cooperate to promote the development of an efficient and sustainable system for ex-situ conservation, and the Seed Vault aspires to become a cornerstone in this emerging global conservation network.
Keywords: Ka; gene bank; genetic resources; safety storage